PERGERSERAN PARADIGMA PENGUNGKAPAN PERUSAHAAN - Rina Asmara (Universitas Bunda Mulia, 2017)
ABSTRAK: The demand of corporate governance consistently and comprehensively increasing, since it is believed that corporate governance implementation will increase the company’s performance and country’s economic condition as a whole. Then corporate governance has a wider and rigorous agenda in the future. What are they? Corporate governance implementation must be able to make every company not only focus on their economic performance, but also including the social, ethical and environment (SEE) issues, and this ‘sustainability reporting’ paradigm must be responded by the company’s management. Every company must disclose not only their financial aspect but also the social and environment aspect within the company. Moreover, the sustainability reporting will become an alternative for the company to show their transparency and accountability toward their stake holders. Key Word : Pergeseran Paradigma, Pengungkapan (disclosure), Corporate Governance, Sustainability Reporting.